MITIGASI PANDEMI COVID-19 BERBASIS KEARIFAN LOKAL DI KABUPATEN OGAN KOMERING ULU - Bianca Virgiana; Dian Novitasari (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
This study aims to determine the mitigation of the COVID-19 pandemic based on local wisdom in the Ogan Komering Ulu district. The main research questions are how the community interacts in dealing with the COVID-19 pandemic and interpreting the forms of local wisdom used by the Ogan ethnic community in handling and preventing the spread of COVID-19. The approach used in this research is qualitative with phenomenological studies. The research subjects are the Ogan ethnic indigenous people who live in Kelumpang Village, Gunung Tiga Village and Ulak Lebar Village. Informants selected through purposive sampling technique. The results showed that the Ogan ethnic community interpreted the covid-19 pandemic as a form of paving the way for the community to utilize natural resources that could be used in handling and preventing COVID-19. The community takes actions based on cultural philosophy in tackling the covid-19 pandemic in the form of using antiseptics made from plants originating from the garden, such as boiled red betel leaves mixed with lime which is useful for killing germs that stick to the body. hand. Take advantage of sunlight when doing farming activities. In addition, it also makes ingredients made from nature which people often call